2020
DOI: 10.1109/access.2020.3006163
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Smoking Event Detection Using a Variational Autoencoder and Neural Decision Forest

Abstract: Smoking is associated with cancer, cardiovascular disease and premature death and can cause severe fire hazards. To assist with smoking cessation, this paper presents a wireless body area networkbased system consisting of two off-the-shelf devices, one smartphone and one smartwatch, to detect smoking events by mining the inertial sensor data from both devices. In the system, an end-to-end trainable unified model is implemented by combining a variational autoencoder with a random forest to classify the collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The data were obtained at 50 samples per second from each phone’s accelerometer, linear acceleration sensor, gyroscope, and magnetometer. Similarly, the SMT dataset [ 35 ] was obtained by recording sensor data at 50 Hz from the three-axis accelerometer and three-axis gyroscope from both a smartphone and wrist-worn device worn by nine participants when performing 12 daily activities. These datasets all have been used and tested in some previous related works and will be utilized for evaluation and analysis here.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were obtained at 50 samples per second from each phone’s accelerometer, linear acceleration sensor, gyroscope, and magnetometer. Similarly, the SMT dataset [ 35 ] was obtained by recording sensor data at 50 Hz from the three-axis accelerometer and three-axis gyroscope from both a smartphone and wrist-worn device worn by nine participants when performing 12 daily activities. These datasets all have been used and tested in some previous related works and will be utilized for evaluation and analysis here.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Shoaib et al [ 9 ] used motion sensors from a smartphone at the right trouser pocket and a smartwatch at the right wrist to recognize 13 different activities, and the results showed that the combination of these two positions outperformed either of them alone. When there are more than two devices worn on the body, it is necessary to use a wireless body area network to integrate sensing, computing, and wireless communication into a unified framework, as in studies [ 10 , 35 ].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, increased research has focused on recognizing smoking activities. Video-based and sensorbased approaches are the two most common methods for classifying smoke occurrences and distinguishing human activities [1,3,7,10,11]. The former examines images or videos from a single camera that contains human motion, whereas the latter examines signal data from sensors like gyroscopes, accelerometers, WiFis and sound sensors [12,13].…”
Section: Related Studiesmentioning
confidence: 99%
“…Systems that can identify when a person is about to relapse anywhere and at any time are required to help kick the habit. The process of mining statistical data such as smoking recurrence can be used to better comprehend smoking patterns [1] and help people to enhance their standard of health and boost their wellness. Inertial sensors are now utilized to track physical activity utilizing wearable intelligent products such as smartwatches.…”
Section: Introductionmentioning
confidence: 99%
“…Typical smartphones are equipped with multiple sensors that are able to collect information such as the user location (Global Positioning System, GPS), identify other people who are near the user (by detecting Bluetooth signals), identifying users’ movements (walking/driving, etc., via onboard accelerometers) and potentially also additional information (such as specific arm movements), if connected to other devices such as smartwatches, which have also shown an accelerating increase in use around the world [ 11 ]. Combining this information with smoking events can enable the characterisation of smoking behaviours to be generated for individual smokers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%